PENGARUH CORPORATE GOVERNANCE, UKURAN DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Ali, Ade Saif; Suripto, Suripto; Sugiyanto, Sugiyanto (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine and obtain empirical evidence of the influence of corporate governance, the size of the board of commissioners and the audit committee on corporate social responsibility disclosure. This type of research is quantitative research and uses secondary data in the form of annual reports & sustainability reports sourced from the official website of the Indonesia Stock Exchange (BEI). The population in this study is the Sri-Kehati index companies listed on the Indonesia Stock Exchange for the 2019-2023 period, with 25 companies as the population and the sample in 5 years of observation. The data analysis technique in this research uses panel data regression analysis in the Eviews 12 software application. The results of this research simultaneously show that corporate governance, the size of the board of commissioners and the audit committee influence disclosure of corporate social responsibility. And partially, corporate governance and the size of the board of commissioners have a significant influence on the scope of corporate social responsibility, while the audit committee does not have a significant influence on the scope of corporate social responsibility.